2017
DOI: 10.32929/2446-8355.2017v26n3p330-346
|View full text |Cite
|
Sign up to set email alerts
|

NÍVEIS DE SOMBREAMENTO NO DESENVOLVIMENTO DE MUDAS DE Hymenaea courbaril var. Stilbocarpa

Abstract: Cada espécie tem exigências próprias para o seu desenvolvimento. Luz, água, temperatura são alguns dos elementos abióticos que influenciam no desenvolvimento das plantas. A luz é importante no desenvolvimento vegetativo por influir, entre outros processos, na taxa de fotossíntese; a intensidade, qualidade, duração e periodicidade da luz agem tanto quantitativa como qualitativamente no incremento da planta. Objetivou-se testar diferentes níveis de sombreamento no desenvolvimento de mudas de jatobá (Hymenaea cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 0 publications
1
3
0
1
Order By: Relevance
“…This fact explains the difference in the crown diameter, where the authors found a mean of 5.9 mm, while in our study, the mean was 3.9 mm. Pagliarini et al (2017) observed that the red net ChromatiNet® did not stimulate stem elongation, flowering, and stomatal conductance alterations as presented in other studies to the light quality that the species 9 needed in the phase evaluated. The red pot significantly influenced the crown diameter and presented increases in the carnation height, evidencing that each species responds differently to sunlight conditions imposed according to their necessities.…”
Section: Discussion Discussion Discussionsupporting
confidence: 72%
“…This fact explains the difference in the crown diameter, where the authors found a mean of 5.9 mm, while in our study, the mean was 3.9 mm. Pagliarini et al (2017) observed that the red net ChromatiNet® did not stimulate stem elongation, flowering, and stomatal conductance alterations as presented in other studies to the light quality that the species 9 needed in the phase evaluated. The red pot significantly influenced the crown diameter and presented increases in the carnation height, evidencing that each species responds differently to sunlight conditions imposed according to their necessities.…”
Section: Discussion Discussion Discussionsupporting
confidence: 72%
“…Regarding the height of the Jatobá plants (Hymenaea courbaril var. Stilbocarpa), there was a significant difference with a 50% and 80% shade screen, because higher shading triggers a superior adaptation mechanism to escape the light deficit (PagliarinI et al, 2017). Brazilian woody seedlings (Caesalpinia echinata Lam.)…”
Section: Resultsmentioning
confidence: 99%
“…courbaril is a climax species whose growth can be limited by low light levels (Oliveira et al, 2011). Thus, according to Pagliarini et al (2017), the best plants are obtained under a shading screen of 30 and 50%. However, excess light is also harmful in this seedling stage.…”
Section: Discussionmentioning
confidence: 99%